2019
DOI: 10.3390/metabo9100212
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of the Tryptophan Pathway Evidences Gender Differences in COPD

Abstract: Increased activity of indoleamine 2,3-dioxygenase (IDO) and tryptophan hydroxylase (TPH) have been reported in individuals with chronic obstructive pulmonary disease (COPD). We therefore investigated the effect of gender stratification upon the observed levels of tryptophan metabolites in COPD. Tryptophan, serotonin, kynurenine, and kynurenic acid were quantified in serum of never-smokers (n = 39), smokers (n = 40), COPD smokers (n = 27), and COPD ex-smokers (n = 11) by liquid chromatography coupled with tande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 54 publications
4
15
0
Order By: Relevance
“…Further quantification of tryptophan and metabolites (serotonin, kynurenine, and kynurenic acid) by LC-MS/ MS in this cohort was also performed. 53 In this exploratory analysis of 38 participants with COPD, 39 neversmokers and 40 smokers without COPD, major differences between tryptophan and metabolites were not seen between men and women. However, an increase in serum serotonin in women better correlated with BAL CD4+ and CD8+ T-cell counts in female but not male smokers suggesting a potential difference in inflammatory pathways as outlined above.…”
Section: Dysregulated Immune Cell Function and Autophagymentioning
confidence: 75%
“…Further quantification of tryptophan and metabolites (serotonin, kynurenine, and kynurenic acid) by LC-MS/ MS in this cohort was also performed. 53 In this exploratory analysis of 38 participants with COPD, 39 neversmokers and 40 smokers without COPD, major differences between tryptophan and metabolites were not seen between men and women. However, an increase in serum serotonin in women better correlated with BAL CD4+ and CD8+ T-cell counts in female but not male smokers suggesting a potential difference in inflammatory pathways as outlined above.…”
Section: Dysregulated Immune Cell Function and Autophagymentioning
confidence: 75%
“…Also, a major limitation is that the study is based only on biopsies from the large airways. In spite of these concerns, the results are significant, and the gender differences are supported by other data blocks from the same cohort [21][22][23][24][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 67%
“…The investigations were performed on specimens from the Karolinska COSMIC cohort (Clinical & Systems Medicine Investigations of Smoking-related Chronic Obstructive Pulmonary Disease) (www.ClinicalTrials.gov/ ct2/show/study/NCT02627872). The cohort has been described in detail previously [21][22][23][24][25][26][27][28][29][30]. The demographics of the included subjects are summarized in Table 1.…”
Section: Study Subjects and Patientsmentioning
confidence: 99%
“…The results from our study suggested a positive relation between kynurenine and tyrosyl-tryptophan and SHS exposure. The kynurenine pathway is responsible for tryptophan metabolism, and 95% of tryptophan is metabolized via the kynurenine pathway [ 38 ]. Therefore, our results suggest a pivotal relationship between tryptophan/kynurenine metabolism and children’s exposure to SHS.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are also studies showing the opposite conclusion. Naz et al found that in chronic obstructive pulmonary disease (COPD) patients, the level of kynurenine, which is the main product of tryptophan [ 44 ], decreased in smokers relative to never-smokers [ 38 ]. Mathai et al [ 45 ] reported that in schizophrenic patients, current smokers showed lower kynurenine levels than past smokers, which further elucidates the neurobiological underpinnings of altered kynurenine levels in smokers.…”
Section: Discussionmentioning
confidence: 99%